Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acsami.1c06668
|View full text |Cite
|
Sign up to set email alerts
|

Shuttle-Shape Carrier-Free Platinum-Coordinated Nanoreactors with O2 Self-Supply and ROS Augment for Enhanced Phototherapy of Hypoxic Tumor

Abstract: The synergistic nanotheranostics of reactive oxygen species (ROS) augment or phototherapy has been a promising method within synergistic oncotherapy. However, it is still hindered by sophisticated design and fabrication, lack of a multimodal synergistic effect, and hypoxia-associated poor photodynamic therapy (PDT) efficacy. Herein, a kind of porous shuttle-shape platinum (IV) methylene blue (Mb) coordination polymer nanotheranostics-loaded 10-hydroxycamptothecin (CPT) is fabricated to address the abovemention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Therefore, the aforementioned experimental results combined with our previous report revealed that PFP possessed the metal− organic polycrystalline structures. 39 Further, the coordinationdriven supramolecular sequential co-assembly capacity of PFP was also estimated via determining the critical aggregation concentration (CAC) value as ca. 4.26 μg/mL (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the aforementioned experimental results combined with our previous report revealed that PFP possessed the metal− organic polycrystalline structures. 39 Further, the coordinationdriven supramolecular sequential co-assembly capacity of PFP was also estimated via determining the critical aggregation concentration (CAC) value as ca. 4.26 μg/mL (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…37,38 To overcome the abovementioned issues, carrier-free metal−organic nanotheranostics such as metal−organic frameworks, coordination polymer nanotheranostics, and metal−organic supramolecular scaffolds have attracted extensive attention since the introduction of dynamic coordination interactions can remarkably enhance their structural integrity and stability. 39,40 Notably, such carrierfree metal−organic nanotheranostics possess on-demand drug release capacity, thereby reducing drug leakage during blood circulation. 41 In addition, the introduction of metal ions with excellent biosafety can expand application functions of nanosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, stimulated by external NIR irradiation and internal lysosomal acidity, the NPs can achieve on-demand release of HCPT to increase in situ mitochondrial ROS and efficient tumor ablation by phototherapy. 272 …”
Section: Inorganic Npsmentioning
confidence: 99%
“…Once they are taken up by tumor cells, the NPs acting as cascade catalysts can effectively catalyze the degradation of endogenous hydrogen peroxide (H 2 O 2 ) into O 2 to alleviate tumor hypoxia. Subsequently, stimulated by external NIR irradiation and internal lysosomal acidity, the NPs can achieve on-demand release of HCPT to increase in situ mitochondrial ROS and efficient tumor ablation by phototherapy 272.…”
mentioning
confidence: 99%
“…38–41 Upon light irradiation, the generated cytotoxic ROS by photosensitizers can oxidize adjacent lipids, amino acids, and nucleotides, and subsequently cause severe and irreversible damage to organelles, finally inducing cell necrosis or apoptosis. 42–45 The combination of chemotherapy and PDT can combat cancer through different mechanisms, thus showing great potency in maximizing the therapeutic efficacy. 46,47…”
Section: Introductionmentioning
confidence: 99%